HISTORICAL AND MODERN BASIS OF CHILD UPBRINGING IN THE FAMILY (Conferencea, 2022)
This article focuses on the main aspects of the educational process and the educational system, and directs adults to the specific goal of educating children in the process of education and thus adapting young people to the complex situations of social life. Is based on the activity.